Subdermal etonogestrel: the effects on menses, general health, religious obligations and sexual relationship - S I, Sharifah A; Abdulwahab, Dalia F; Awang, Mokhtar (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia., 2015)
Objective: The aim of this study is to determine the effects of subdermal etonogestrel implant on menstrual pattern, body mass index (BMI), systolic and diastolic blood pressure (SBP and DBP), sexual relationship and religious obligations. Methodology: A descriptive study was conducted at a family planning clinic between 1st January 2010 to 31st December 2011 whereby all the women who had their subdermal etonogestrel removed during this period were included. A selfprepared questionnaire was filled up with the help of a research assistant, which looked into the menstrual cycles prior to and during the implant usage, the non-menstrual adverse events, effect of menses on religious obligations and sexual relationship and the overall acceptability of subdermal etonogestrel as a contraceptive method. Blood pressure (BP) and BMI were recorded at the time of removal, while BP and BMI at insertion were gathered from the case file. Result: 50 patients were recruited in this study. The mean duration of use was 33.8 months (±10.4) and 78% had completed 3 years. The prevalence of menstrual disturbance whilst on subdermal etonogestrel implant was 78%. The mean differences of SBP, DBP and BMI at removal and prior to usage were statistically significant. There was no association between BMI and menstrual pattern whilst on implant. Practicing religious obligations and sexual activity were affected in 14.0% and 18.0% respectively. Overall satisfaction of subdermal implant was 92%. Conclusion: Despite the high prevalence of menstrual disturbance, subdermal etonogestrel is well accepted. Changes in the mean of SBP, DBP and BMI were not clinically significant, but a significant proportion of the studied women had a significant increase in SBP, DBP and BMI. The performing of religious duty and sexual activity seem to be unaffected.